Resin composition

JP2025001412AActive Publication Date: 2025-01-08AJINOMOTO CO INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023100989
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2025-01-08
Estimated Expiration
2043-06-20

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、良好な耐折性と絶縁信頼性を呈すると共に、耐熱特性(リフロー後の下地密着性)も良好である硬化物をもたらすことができる、新規の樹脂組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001412000001
    Figure 2025001412000001
  • Figure 2025001412000002
    Figure 2025001412000002
  • Figure 2025001412000003
    Figure 2025001412000003
Patent Text Reader

Abstract

To provide a resin composition which provides a cured product that exhibits good folding resistance and insulation reliability, and also has good heat resistant characteristics (substrate adhesion after reflow).SOLUTION: A resin composition contains a thermosetting resin, an inorganic filler and an oligophenylene ether skeleton-containing resin X having a glass transition temperature of 25°C or lower, wherein a cured product of the resin composition exhibits a dielectric loss tangent Df of less than 0.01, and satisfies at least one of the following conditions (1) and (2). (1) Elongation is 5% or more and less than 50%. (2) The folding endurance number in an MIT folding endurance test is 200 times or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, and further to a resin sheet, a cured product, a flexible substrate, and a semiconductor device. [Background technology]

[0002] With the recent development of diverse semiconductor package structures, there is an increasing need for high-speed communication and high multi-layering in the interlayer insulating materials of bendable semiconductor package substrates, and there is an increasing need for insulating materials with low dielectric tangent, insulation reliability, and heat resistance (adhesion to conductors after reflow).

[0003] Conventionally, insulating materials containing soft resins have been used to ensure bendability (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-21851 A Summary of the Invention [Problem to be solved by the invention]

[0005] On the other hand, adding a soft resin to the extent that it ensures bending (folding resistance) results in an insulating material with poor reliability and heat resistance, which means that there is a trade-off between bending, insulating reliability, and heat resistance.

[0006] An object of the present invention is to provide a resin composition which provides a cured product having good folding endurance and insulation reliability as well as good heat resistance (adhesion to the base after reflow). [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive research and have found that the above-mentioned problems can be solved by a resin composition having the following configuration, which contains a thermosetting resin, an inorganic filler, and a resin containing a specific oligophenylene ether skeleton (hereinafter also referred to as an "oligophenylene ether skeleton-containing resin") and exhibits specific physical properties after curing, and have thus completed the present invention.

[0008] That is, the present invention includes the following. [1] thermosetting resin, Inorganic fillers, and Oligophenylene ether skeleton-containing resin X having a glass transition temperature of 25°C or lower A resin composition comprising: A resin composition, the cured product of which exhibits a dielectric loss tangent Df of less than 0.01 and satisfies at least one of the following conditions (1) and (2): (1) Elongation is 5% or more but less than 50% (2) MIT folding endurance test: 200 or more folding cycles [2] The resin composition according to [1], wherein the content of the resin X is 20% by mass or more and less than 85% by mass, when the resin component in the resin composition is 100% by mass. [3] The resin composition according to [1] or [2], wherein the content of the inorganic filler is 50 mass% or less when the non-volatile components in the resin composition are 100 mass%. [4] The resin composition according to any one of [1] to [3], wherein Resin X contains one or more structural units selected from the group consisting of polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic structural units, and polysiloxane structural units. [5] The resin composition according to any one of [1] to [4], wherein the resin X contains a cyclic imide structure. [6] The resin composition according to any one of [1] to [5], which is for forming an insulating layer of a flexible substrate. [7] A cured product of the resin composition according to any one of [1] to [6]. [8] A resin sheet comprising a support and a layer of the resin composition according to any one of [1] to [6] provided on the support. [9] The resin sheet according to [8], wherein the support is a thermoplastic resin film or a metal foil.

[10] A flexible substrate comprising an insulating layer made of a cured product of the resin composition according to any one of [1] to [6].

[11] A semiconductor device comprising the flexible substrate according to

[10] . Effect of the Invention

[0009] According to the present invention, it is possible to provide a novel resin composition that can give a cured product that exhibits good folding endurance and insulation reliability as well as good heat resistance characteristics (adhesion to the base after reflow). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Terminology explanation> As used herein, the term "optionally substituted" in reference to a compound or group means both the case where none of the hydrogen atoms of the compound or group are substituted with a substituent, and the case where some or all of the hydrogen atoms of the compound or group are substituted with a substituent.

[0011] In this specification, unless otherwise specified, the term "substituent" means a halogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an alkoxy group, a cycloalkyloxy group, an aryl group, an aryloxy group, an arylalkyl group, an arylalkoxy group, a monovalent heterocyclic group, an alkylidene group, an amino group, a silyl group, a carboxy group, a sulfo group, a cyano group, a nitro group, a hydroxy group, a mercapto group, and an oxo group.

[0012] Examples of halogen atoms used as a substituent include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. The alkyl group used as a substituent may be either linear or branched. The number of carbon atoms in the alkyl group is preferably 1 to 12, more preferably 1 to 6, and even more preferably 1 to 3. The alkenyl group used as a substituent may be either linear or branched. The number of carbon atoms in the alkenyl group is preferably 2 to 12, more preferably 2 to 6, and even more preferably 2 or 3. The number of carbon atoms in the cycloalkyl group used as a substituent is preferably 3 to 12, more preferably 3 to 6. The alkoxy group used as a substituent may be either linear or branched. The number of carbon atoms in the alkoxy group is preferably 1 to 12, more preferably 1 to 6. The number of carbon atoms in the cycloalkyloxy group used as a substituent is preferably 3 to 12, more preferably 3 to 6. The aryl group used as a substituent is a group obtained by removing one hydrogen atom on the aromatic ring from an aromatic hydrocarbon. The number of carbon atoms in the aryl group used as a substituent is preferably 6 to 14, more preferably 6 to 10. The number of carbon atoms of the aryloxy group used as a substituent is preferably 6 to 14, more preferably 6 to 10. The number of carbon atoms of the arylalkyl group used as a substituent is preferably 7 to 15, more preferably 7 to 11. The number of carbon atoms of the arylalkoxy group used as a substituent is preferably 7 to 15, more preferably 7 to 11. The monovalent heterocyclic group used as a substituent refers to a group in which one hydrogen atom is removed from the heterocycle of a heterocyclic compound. The number of carbon atoms of the monovalent heterocyclic group is preferably 3 to 15, more preferably 3 to 9. The alkylidene group used as a substituent refers to a group in which two hydrogen atoms are removed from the same carbon atom of an alkane. The number of carbon atoms of the alkylidene group is preferably 1 to 12, more preferably 1 to 6, and even more preferably 1 to 3. The above-mentioned substituent may further have a substituent (hereinafter sometimes referred to as a "secondary substituent"). Unless otherwise specified, the same one as the above-mentioned substituent may be used as the secondary substituent.

[0013] Hereinafter, the present invention will be described in detail with reference to embodiments and examples. However, the present invention is not limited to the following embodiments and examples, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0014] [Resin composition] The resin composition of the present invention comprises thermosetting resin, Inorganic filler, and Oligophenylene ether skeleton-containing resin X having a glass transition temperature of 25°C or lower A resin composition comprising: a cured product of the resin composition exhibits a dielectric loss tangent Df of less than 0.01 and satisfies the following conditions (1) and (2): (1) Elongation is 5% or more but less than 50% (2) MIT folding endurance test: 200 or more folding cycles The present invention is characterized in that at least one of the above is satisfied.

[0015] As mentioned above, there is a growing need for high-speed communication and high multi-layering in interlayer insulating materials for bendable semiconductor package substrates, and there is an increasing need for good dielectric properties (low dielectric tangent), insulation reliability, and heat resistance (substrate adhesion after reflow). In this regard, there was a problem that blending a soft resin to an extent that ensures bendability (folding resistance) resulted in an insulating material with poor reliability and heat resistance. In other words, there was a trade-off between bendability, insulation reliability, and heat resistance.

[0016] In contrast, the resin composition of the present invention, which contains an oligophenylene ether skeleton-containing resin X having a glass transition temperature of 25° C. or less in combination with a thermosetting resin and an inorganic filler, exhibits a dielectric loss tangent Df of less than 0.01 after curing, and satisfies the conditions related to specific mechanical properties, can provide a cured product that exhibits good folding resistance and insulation reliability, as well as good heat resistance properties (adhesion to the substrate after reflow). Thus, the resin composition of the present invention can advantageously achieve a reduction in transmission loss during operation in a high-frequency environment, which is required for next-generation high-speed communication, and significantly contributes to realizing a flexible substrate that satisfies both insulation reliability and heat resistance properties.

[0017] Each component will be described below.

[0018] <Thermosetting resin> The resin composition of the present invention contains a thermosetting resin.

[0019] Examples of the thermosetting resin include, but are not limited to, epoxy resin, benzocyclobutene resin, epoxy acrylate resin, urethane acrylate resin, urethane resin, cyanate resin, polyimide resin, benzoxazine resin, unsaturated polyester resin, melamine resin, silicone resin, etc. Among them, it is preferable to contain an epoxy resin from the viewpoint of providing a cured product that exhibits good folding resistance and insulation reliability and also has good heat resistance characteristics (adhesion to the base after reflow) in combination with an inorganic filler and an oligophenylene ether skeleton-containing resin X described later.

[0020] The type of epoxy resin is not particularly limited as long as it has one or more (preferably two or more) epoxy groups in one molecule. Examples of epoxy resins include bisphenol type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, and tetraphenylethane type epoxy resins. Bisphenol type epoxy resin refers to an epoxy resin having a bisphenol structure, such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, and bisphenol AF type epoxy resin. Biphenyl type epoxy resin refers to an epoxy resin having a biphenyl structure, where the biphenyl structure may have a substituent such as an alkyl group, an alkoxy group, or an aryl group. Therefore, bixylenol type epoxy resin and biphenyl aralkyl type epoxy resin are also included in biphenyl type epoxy resin.

[0021] Epoxy resins can be classified into epoxy resins that are liquid at a temperature of 20°C (hereinafter referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20°C (hereinafter referred to as "solid epoxy resins"). The resin composition of the present invention may contain only a liquid epoxy resin, may contain only a solid epoxy resin, or may contain a combination of a liquid epoxy resin and a solid epoxy resin.

[0022] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0023] As the liquid epoxy resin, glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane dimethanol type epoxy resin, cyclic aliphatic glycidyl ether, and epoxy resin having a butadiene structure are preferred.

[0024] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX Corporation, "YX7400" and "YX7400N" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; and "jER807" manufactured by Mitsubishi Chemical Corporation. "1750" (bisphenol F type epoxy resin); "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L" and "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA Corporation; "EP-4088S" ( Dicyclopentadiene type epoxy resin; "ZX1059" manufactured by Nippon Steel Chemical & Material Co., Ltd. (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); "EX-721" manufactured by Nagase ChemteX Co., Ltd. (glycidyl ester type epoxy resin); "EX-991L" manufactured by Nagase ChemteX Co., Ltd. (alkyleneoxy skeleton and butadiene skeleton-containing epoxy resin); "Celloxide 2021P" manufactured by Daicel Co., Ltd. (alicyclic epoxy resin with ester skeleton) epoxy resin); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins having a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EG-280" (fluorene structure-containing epoxy resin) manufactured by Osaka Gas Chemicals Co., Ltd.; and "EX-201" (cyclic aliphatic glycidyl ether) manufactured by Nagase ChemteX Corporation.

[0025] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.

[0026] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, and phenolphthalimidine type epoxy resins.

[0027] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; "EXA-7311" and "E XA-7311-G3, EXA-7311-G4, EXA-7311-G4S, HP-6000, HP-6000L (naphthylene ether type epoxy resin); Nippon Kayaku's "EPPN-502H" (trisphenol type epoxy resin); Nippon Kayaku's "NC7000L" (naphthol novolac type epoxy resin); Nippon Kayaku's "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin); Nippon Steel Chemical & Material's "ESN475V" , "ESN4100V" (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd. Examples of epoxy resins that can be used include "YX7700" (phenol aralkyl type epoxy resin) manufactured by Osaka Gas Chemicals; "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.These may be used alone or in combination of two or more.

[0028] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, the mass ratio thereof (liquid epoxy resin:solid epoxy resin) is preferably 10:1 to 1:10, more preferably 5:1 to 1:5, even more preferably 3:1 to 1:2, and particularly preferably 2:1 to 1:1.

[0029] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., even more preferably 70 g / eq. to 1,000 g / eq., and even more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0030] The weight average molecular weight of the epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and further preferably 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0031] The content of the thermosetting resin in the resin composition is not particularly limited, but is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 6% by mass or more, 8% by mass or more, or 10% by mass or more, when the resin component in the resin composition is 100% by mass. The upper limit of the content is not particularly limited and may be determined depending on the properties required for the resin composition, but may be, for example, 60% by mass or less, 50% by mass or less, or 40% by mass or less.

[0032] In the present invention, the "resin component" of the resin composition refers to the non-volatile components constituting the resin composition excluding the inorganic filler described above.

[0033] <Inorganic filler> The resin composition of the present invention contains an inorganic filler. By containing the inorganic filler, it is possible to reduce the thermal expansion coefficient and the dielectric loss tangent.

[0034] Examples of inorganic fillers include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum silicate, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferred as the silica. The inorganic filler may be used alone or in combination of two or more.

[0035] Examples of commercially available inorganic fillers include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Corporation; "Cellspheres" and "MGH-005" manufactured by Pacific Cement Corporation; and "Sferique" and "BA-1" manufactured by JGC Catalysts and Chemicals Co., Ltd.

[0036] The average particle size of the inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, 2 μm or less, 1 μm or less, or 0.7 μm or less. The lower limit of the average particle size is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.07 μm or more, 0.1 μm or more, or 0.2 μm or more. The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample is measured using a laser diffraction particle size distribution measuring device with blue and red light source wavelengths used, and the volume-based particle size distribution of the inorganic filler is measured using a flow cell method, and the average particle size is calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0037] The specific surface area of ​​the inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, 3m 2 / g or more or 5m 2 The upper limit of the specific surface area is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 80m 2 / g or less, more preferably 60m 2 / g or less, 50m 2 / g or less or 40m 2 / g or less. The specific surface area of ​​the inorganic filler is obtained according to the BET method by adsorbing nitrogen gas onto the surface of the sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountec Co., Ltd.) and calculating the specific surface area using the BET multipoint method.

[0038] The inorganic filler is preferably surface-treated with a suitable surface treatment agent. By performing the surface treatment, the moisture resistance and dispersibility of the inorganic filler can be improved. Examples of the surface treatment agent include silane coupling agents such as vinyl silane coupling agents, epoxy silane coupling agents, styryl silane coupling agents, (meth)acrylic silane coupling agents, amino silane coupling agents, isocyanurate silane coupling agents, ureido silane coupling agents, mercapto silane coupling agents, isocyanate silane coupling agents, and acid anhydride silane coupling agents; non-silane coupling-alkoxysilane compounds such as methyltrimethoxysilane and phenyltrimethoxysilane; and silazane compounds. The surface treatment agent may be used alone or in combination of two or more.

[0039] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), and Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane).

[0040] The degree of surface treatment with the surface treatment agent is preferably within a predetermined range from the viewpoint of improving the dispersibility of the inorganic filler. Specifically, it is preferable that 100% by mass of the inorganic filler is surface-treated with 0.2 to 5% by mass of the surface treatment agent.

[0041] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition or the melt viscosity in the form of a sheet, it is more preferable that the melt viscosity is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is more preferable. The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, an "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0042] In order to obtain a cured product that exhibits good folding resistance and insulation reliability in combination with resin X and also has good heat resistance (adhesion to the substrate after reflow), the content of the inorganic filler in the resin composition is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 44% by mass or less, 42% by mass or less, or 40% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. According to the present invention using the oligophenylene ether skeleton-containing resin X described below, the lower limit of the content of the inorganic filler is not particularly limited, and may be, for example, 5% by mass or more, 10% by mass or more, 15% by mass or more, etc.

[0043] <Oligophenylene ether skeleton-containing resin X> The resin composition of the present invention contains an oligophenylene ether skeleton-containing resin X (also simply referred to as "resin X") having a glass transition temperature of 25°C or lower. Here, the glass transition temperature of resin X being 25° C. or lower means that if resin X has only one glass transition temperature, that glass transition temperature is 25° C. or lower, and if resin X has multiple glass transition temperatures, at least one of the glass transition temperatures is 25° C. or lower. By using such resin X in combination with a thermosetting resin and an inorganic filler, it is possible to realize a resin composition that provides a cured product that exhibits good folding resistance and insulation reliability as well as good heat resistance characteristics (adhesion to base after reflow).

[0044] -Oligophenylene ether skeleton- Resin X preferably contains an oligophenylene ether skeleton containing a plurality of phenylene ether units represented by the following formula (1).

[0045] [ka] (In formula (1), R each independently represents a halogen atom, an optionally substituted alkyl group, an optionally substituted alkoxy group, an optionally substituted aryl group, an optionally substituted amino group, a nitro group, or a carboxy group; m represents an integer of 0 to 4.

[0046] The alkyl group or alkoxy group in R may be either linear or branched, and has preferably 1 to 10 carbon atoms, more preferably 1 to 6, and further preferably 1 to 4 or 1 to 3. The number of carbon atoms does not include the number of carbon atoms of the substituent.

[0047] The number of carbon atoms in the aryl group for R is preferably 6 to 14, and more preferably 6 to 10. The number of carbon atoms does not include the number of carbon atoms of the substituent.

[0048] The substituent that the monovalent group represented by R may have is as described above, and among them, it is preferably one or more selected from a halogen atom, an alkyl group, an alkoxy group, and an aryl group, more preferably one or more selected from a halogen atom, an alkyl group, and an aryl group, and further preferably one or more selected from a fluorine atom, an alkyl group having 1 to 6 carbon atoms, and an aryl group having 6 to 10 carbon atoms.

[0049] In formula (1), m represents an integer of 0 to 4, preferably an integer of 0 to 3, and more preferably an integer of 1 to 3.

[0050] In terms of providing a cured product that exhibits good folding endurance and insulation reliability as well as good heat resistance (adhesion to substrate after reflow) in combination with a thermosetting resin and an inorganic filler, the oligophenylene ether skeleton is preferably an oligophenylene ether skeleton containing one or more units selected from the group consisting of a 2,6-disubstituted-1,4-phenylene ether unit, a 2,5-disubstituted-1,4-phenylene ether unit, and a 2,3,6-trisubstituted-1,4-phenylene ether unit, and particularly preferably an oligophenylene ether skeleton containing a plurality of 2,6-disubstituted-1,4-phenylene ether units (wherein the substituents at the 2,6-positions, the substituents at the 2,5-positions, and the substituents at the 2,3,6-positions correspond to R in formula (1)).

[0051] Specific examples of suitable oligophenylene ether skeletons include oligo(2,6-disubstituted-1,4-phenylene ether) skeletons such as oligo(2,6-dialkyl-1,4-phenylene ether) skeletons, oligo(2-alkyl-6-aryl-1,4-phenylene ether) skeletons, oligo(2,6-diaryl-1,4-phenylene ether) skeletons, and oligo(2,6-dihalo-1,4-phenylene ether) skeletons; 2,6-disubstituted phenols and other phenol compounds (e.g., 2,5-dialkyl phenols); and 2,3,6-trisubstituted phenols such as 2,3,6-trialkylphenol and 2,3,6-trihalophenol; and oligophenylene ether skeletons containing a plurality of 2,6-disubstituted-1,4-phenylene ether units, such as a skeleton having a copolymer structure with 2,5-disubstituted phenols such as 2,5-diphenylphenol, 2-alkyl-5-arylphenol, and 2,5-diarylphenol; and 2,3,6-trisubstituted phenols such as 2,3,6-trialkylphenol and 2,3,6-trihalophenol; and a coupling reaction product of 2,6-disubstituted phenol with a biphenol compound or a bisphenol compound.

[0052] In order to provide a cured product that exhibits good folding endurance and insulation reliability as well as good heat resistance (adhesion to the base after reflow) in combination with a thermosetting resin and an inorganic filler, it is preferable that the resin X contains a structure represented by the following formula (2) as an oligophenylene ether skeleton.

[0053] [ka] (In formula (2), R and m have the same meanings as above. L represents a divalent linking group. n1 and n2 each independently represent an integer of 1 to 100.

[0054] In formula (2), L represents a divalent linking group. Examples of the divalent linking group include a single bond, an alkylene group which may have a substituent, an alkenylene group which may have a substituent, an arylene group which may have a substituent, an alkylarylene group which may have a substituent, a heteroarylene group which may have a substituent, -O-, -NH-, -NRx Examples of the divalent group include -, -CO-, -CS-, -SO-, -SO2-, -C(=O)O-, -NHC(=O)-, -NC(=O)N-, -NHC(=O)O-, -C(=O)-, -S-, and divalent groups formed by combining a plurality of these. x represents a hydrocarbon group having 1 to 12 carbon atoms.

[0055] Among these, from the viewpoint of obtaining the effects of the present invention more effectively, the divalent linking group represented by L is preferably a single bond, an alkylene group which may have a substituent, an alkenylene group which may have a substituent, an arylene group which may have a substituent, -O-, -NR x Preferred are -, -CO-, -CS-, -SO-, -SO2-, and divalent groups formed by combining a plurality of these, and more preferred are a single bond, an alkylene group which may have a substituent, an arylene group which may have a substituent, and divalent groups formed by combining a plurality of these.

[0056] The substituent that the divalent group in L may have is as described above, but from the viewpoint of further enjoying the effects of the present invention, it is preferably one or more selected from a halogen atom and a hydrocarbon group, more preferably one or more selected from a halogen atom, an alkyl group, and an aryl group, and even more preferably one or more selected from a fluorine atom, an alkyl group having 1 to 6 carbon atoms, and an aryl group having 6 to 10 carbon atoms.

[0057] The divalent linking group represented by L preferably has 60 or less carbon atoms, more preferably 48 or less, even more preferably 36 or less, and even more preferably 24 or less carbon atoms.

[0058] Among these, from the viewpoint of providing a cured product that exhibits good folding endurance and insulation reliability as well as good heat resistance (adhesion to the base after reflow) in combination with a thermosetting resin and an inorganic filler, the divalent linking group represented by L is preferably an alkylene group having 1 to 6 carbon atoms or a divalent group represented by the following formula (3):

[0059] [ka] (In formula (3), R 1 ~R 8 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group; * represents a bond.)

[0060] In formula (3), R 1 ~R 8 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group. Among these, from the viewpoint of obtaining the effects of the present invention, R 1 , R 2 , R 7 and R 8 Preferably, R represents an alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 4 carbon atoms. 3 and R 4 Among these, it is preferable that one of them represents a hydrogen atom and the other represents an alkyl group having 1 to 6 carbon atoms, and R 5 and R 6 Of these, it is preferable that one represents a hydrogen atom and the other represents an alkyl group having 1 to 6 carbon atoms.

[0061] In formula (2), R and m are as described above for the phenylene ether unit of formula (1). Among them, the phenylene ether unit constituting the oligophenylene ether skeleton represented by formula (2) is preferably a 2,6-disubstituted-1,4-phenylene ether unit, more preferably a 2,6-dialkyl-1,4-phenylene ether unit, a 2-alkyl-6-aryl-1,4-phenylene ether unit, a 2,6-diaryl-1,4-phenylene ether unit, or a 2,6-dihalo-1,4-phenylene ether unit, from the viewpoint of being able to enjoy the effects of the present invention.

[0062] In order to provide a cured product that exhibits good folding endurance and insulation reliability as well as good heat resistance (adhesion to the base after reflow) in combination with a thermosetting resin and an inorganic filler, it is preferable that the resin X contains a structure represented by the following formula (2-1) as an oligophenylene ether skeleton.

[0063] [ka] (In formula (2-1), R, L, n1, and n2 have the same meanings as above.)

[0064] In formula (2-1), R, L, n1, and n2 have the same meanings as above, and preferred examples thereof are as described above. Among them, from the viewpoint of further enjoying the effects of the present invention, R each independently preferably represents a halogen atom, an alkyl group, or an aryl group, more preferably represents a halogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms, and further preferably represents an alkyl group having 1 to 6 carbon atoms; L is a single bond, an alkylene group which may have a substituent, an alkenylene group which may have a substituent, an arylene group which may have a substituent, -O-, -NR x -, -CO-, -CS-, -SO-, -SO2-, and a divalent group formed by combining a plurality of these are preferred, a single bond, an alkylene group which may have a substituent, an arylene group which may have a substituent, and a divalent group formed by combining a plurality of these are more preferred, and an alkylene group having 1 to 6 carbon atoms or a divalent group represented by the above formula (3) is even more preferred, n1 and n2 each independently represent an integer in the range of 1 to 100, and preferably represent an integer in a range such that at least one glass transition temperature of resin X is 25° C. or lower, more preferably such that a suitable condition (the condition will be described later) is satisfied in relation to the flexible backbone described later, and further such that a suitable condition (the condition will be described later) for the weight average molecular weight of resin X is satisfied.

[0065] -Flexible skeleton- Resin X contains, in addition to an oligophenylene ether skeleton, which is a rigid skeleton, a skeleton (also simply referred to as a "flexible skeleton") that is more flexible than the oligophenylene ether skeleton.

[0066] From the viewpoint of providing a cured product that exhibits better folding resistance and insulation reliability as well as better heat resistance (adhesion to substrate after reflow) in combination with a thermosetting resin and an inorganic filler, it is preferred that Resin X contains, as a flexible skeleton, one or more structural units selected from the group consisting of polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic structural units, and polysiloxane structural units.

[0067] Examples of polyolefin structural units include polyethylene structural units, polypropylene structural units, polybutadiene structural units, hydrogenated polybutadiene structural units, polyisopropylene structural units, hydrogenated polyisopropylene structural units, etc. Here, the term "hydrogenated polybutadiene structural units" refers to polybutadiene structural units in which some or all of the unsaturated bonds have been hydrogenated, and similarly, the term "hydrogenated polyisoprene structural units" refers to polyisoprene structural units in which some or all of the unsaturated bonds have been hydrogenated.

[0068] The polyolefin structural unit may be, for example, a structural unit remaining after removing two or more hydroxyl groups from a polyolefin structure-containing polyol compound when resin X is produced using a polyol compound having a flexible backbone as described below (in this embodiment, a polyolefin structure-containing polyol compound). The polyolefin structure-containing polyol compound may be a commercially available product, and examples of the commercially available product include "G-1000", "G-2000", and "G-3000" (polybutadiene with hydroxy groups at both ends), "GI-1000", "GI-2000", and "GI-3000" (polybutadiene with hydrogenated hydroxy groups at both ends) manufactured by Nippon Soda Co., Ltd.

[0069] Examples of the polycarbonate structural unit include aliphatic polycarbonates (polyethylene carbonate, polypropylene carbonate, polybutylene carbonate, polycyclohexane carbonate, etc.), and aromatic polycarbonates (polybisphenol A carbonate, polybisphenol F carbonate, polybisphenol S carbonate, etc.).

[0070] The polycarbonate structural unit may be, for example, a structural unit remaining after removing two or more hydroxyl groups from a polycarbonate structure-containing polyol compound when resin X is produced using a polyol compound having a flexible backbone as described below (polycarbonate structure-containing polyol compound in this embodiment). The polycarbonate structure-containing polyol compound may be a commercially available product, and examples of the commercially available product include "T6002" and "T6001" (polycarbonate with hydroxyl groups at both ends) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2015N", "C-2090", and "C-3090" (polycarbonate with hydroxyl groups at both ends) manufactured by Kuraray Co., Ltd.

[0071] Examples of the polyether structural unit include a polyethylene glycol structural unit, a polypropylene glycol structural unit, a polytetramethylene glycol structural unit, and a polybutylene glycol structural unit.

[0072] The polyether structural unit may be, for example, a structural unit remaining after removing two or more hydroxyl groups from a polyol compound having a flexible backbone as described below (a polyol compound containing a polyether structure in this embodiment) when resin X is produced using the polyol compound containing a polyether structure. The polyol compound containing a polyether structure may be a commercially available product, and examples of the commercially available product include "Pronon #102", "Pronon #104", "Pronon #201", "Pronon #202B", "Pronon #204", "Pronon #208", "Unilube 70DP-600B", and "Unilube 70DP-950B" (polyethylene glycol-polypropylene glycol copolymers) manufactured by NOF Corporation, and "Pluronic (registered trademark) L-23", "Pluronic L-31", "Pluronic L-44", "Pluronic L-61", and "ADEKA Pluronic L- 62", "Pluronic L-64", "Pluronic L-71", "Pluronic L-72", "Pluronic L-101", "Pluronic L-121", "Pluronic P-84", "Pluronic P-85", "Pluronic P-103", "Pluronic F-68", "Pluronic F-88", "Pluronic F-108", "Pluronic 25R-1", "Pluronic 25R-2", "Pluronic 17R-2", "Pluronic 17R-3", and "Pluronic 17R-4" (polyethylene glycol-polypropylene glycol copolymer).

[0073] Examples of the polyester structural unit include a polyethylene terephthalate structural unit, a polybutylene terephthalate structural unit, a polyethylene naphthalate structural unit, a polybutylene naphthalate structural unit, and a polytrimethylene terephthalate structural unit.

[0074] The polyester structural unit may be, for example, a remaining structural unit obtained by removing two or more hydroxyl groups from a polyol compound having a flexible backbone (polyester structure-containing polyol compound in this embodiment) as described later when resin X is produced. The polyester structure-containing polyol compound may be a commercially available product, and examples of the commercially available product include Vylon (registered trademark) manufactured by Toyobo Co., Ltd., Polyester (registered trademark) manufactured by Nippon Synthetic Chemical Industry Co., Ltd., and Slack (registered trademark) manufactured by Hitachi Chemical Polymer Co., Ltd.

[0075] The poly(meth)acrylic structural unit means a structural unit containing at least one of acryl and methacryl structures. For example, when resin X is produced using a polyol compound having a flexible backbone (in this embodiment, a poly(meth)acrylic structure-containing polyol compound) as described later, the poly(meth)acrylic structural unit may be a remaining structural unit obtained by removing two or more hydroxyl groups from the poly(meth)acrylic structure-containing polyol compound. The poly(meth)acrylic structure-containing polyol compound may be a commercially available product, and examples of the commercially available product include Teisan Resin "SG-600TEA" and "SG-790" (hydroxyl group-containing acrylic acid ester copolymer resin) manufactured by Nagase ChemteX Corporation, and "W-197C" (hydroxyl group-containing acrylic acid ester copolymer resin) manufactured by Negami Chemical Industries, Ltd.

[0076] Examples of the polysiloxane structural unit include a dialkylpolysiloxane structural unit, a diarylpolysiloxane structural unit, a monoalkylmonoarylpolysiloxane structural unit, and a monoalkylpolysiloxane structural unit.

[0077] The polysiloxane structural unit may be, for example, a structural unit remaining after removing two or more hydroxyl groups from a polyol compound containing a polysiloxane structure, when resin X is produced using a polyol compound having a flexible backbone as described below (a polyol compound containing a polysiloxane structure in this embodiment). The polyol compound containing a polysiloxane structure may be a commercially available product, and examples of the commercially available product include "X-21-5841" and "KF-9701" (polysiloxane with hydroxyl groups at both ends) manufactured by Shin-Etsu Chemical Co., Ltd.

[0078] Resin X contains an oligophenylene ether skeleton and a flexible skeleton as described above. The mass ratio of the oligophenylene ether skeleton to the flexible skeleton in resin X (flexible skeleton / oligophenylene ether skeleton) is preferably 0.2 or more, more preferably 0.4 or more, even more preferably 0.5 or more, 0.6 or more, or 0.7 or more, from the viewpoint of providing a cured product that can further suppress warping in combination with a thermosetting resin and an inorganic filler, exhibits better dielectric properties, and maintains better mechanical strength even when exposed to a high-temperature and high-humidity environment. The condition of the mass ratio can be, for example, 3 or less, 2.5 or less, 2 or less, etc.

[0079] Resin X has a glass transition temperature of 25°C or less. If resin X has only one glass transition temperature, the glass transition temperature is 25°C or less, and if resin X has multiple glass transition temperatures, at least one of the glass transition temperatures is 25°C or less. If resin X has multiple glass transition temperatures, there is no particular restriction on the other glass transition temperatures as long as the resin X has a glass transition temperature of 25°C or less. In combination with a thermosetting resin and an inorganic filler, from the viewpoint of providing a cured product that exhibits better folding resistance and insulation reliability as well as better heat resistance characteristics (substrate adhesion after reflow), the glass transition temperature of resin X of 25°C or less is preferably 10°C or less, more preferably 5°C or less, and even more preferably 0°C or less.

[0080] In the present invention, the glass transition temperature of resin X is based on a value measured by DSC (differential scanning calorimetry) at a heating rate of 5° C. / min.

[0081] From the viewpoint of enjoying the effects of the present invention, the weight average molecular weight Mw of the resin X is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 20,000 or more, 40,000 or more, 60,000 or more, 80,000 or more, or 100,000 or more. The upper limit of the Mw is not particularly limited, but is usually less than 1,000,000, preferably less than 800,000, more preferably less than 600,000, and even more preferably less than 500,000.

[0082] In the present invention, the weight average molecular weight Mw of the resin X is based on a polystyrene equivalent value measured by gel permeation chromatography (GPC).

[0083] -Synthesis of Resin X- There are no particular limitations on the synthesis procedure for resin X, so long as it is possible to achieve a structure containing the above-mentioned oligophenylene ether skeleton and flexible skeleton.

[0084] An example of the synthesis procedure for resin X is shown below.

[0085] In one embodiment, resin X is (x1) a polyol compound having a flexible skeleton; (x2) a polyisocyanate compound; (x3) an acid anhydride group-containing compound; (x4) a polyol compound containing an oligophenylene ether skeleton; It is obtained by reacting

[0086] In this reaction, the flexible skeleton of the component (x1) and the oligophenylene ether skeleton of the component (x4) are bonded via an imide structure (preferably a cyclic imide structure) formed by the reaction of the components (x2) and (x3). Thus, in one embodiment, the resin X includes an imide structure (preferably a cyclic imide structure).

[0087] As for the (x1) component, suitable examples of the flexible skeleton are as described above. As the (x1) component, any polyol compound containing a flexible skeleton may be used depending on the structure of the target resin X (i.e., the flexible skeleton), and examples of commercially available products thereof are as described above in relation to the flexible skeleton. As for the (x1) component, depending on the type of the flexible skeleton contained in the resin X, one type may be used alone, or two or more types may be used in combination.

[0088] The polyisocyanate compound of the component (x2) is not particularly limited in type, so long as it reacts with a hydroxy group and with the component (x3) to form an imide structure. Examples of the polyisocyanate compound include aliphatic diisocyanate compounds such as butane diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate; alicyclic diisocyanate compounds such as norbornane diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate; phenylene diisocyanate (p-phenylene diisocyanate, m-phenylene diisocyanate), xylylene diisocyanate (p-xylylene diisocyanate, m-xylylene diisocyanate), toluene diisocyanate, and the like. Examples of the diisocyanate include aromatic diisocyanate compounds such as toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, 4,4'-diphenylmethane diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, 3,3'-diethyldiphenyl-4,4'-diisocyanate, m-xylene diisocyanate, 1,3-bis(α,α-dimethylisocyanatomethyl)benzene, tetramethylxylylene diisocyanate, diphenylene ether-4,4'-diisocyanate, and naphthalene diisocyanate; polymethylene polyphenyl polyisocyanate; and isocyanurate-modified, biuret-modified, and allophanate-modified compounds thereof. The component (x2) may be used alone or in combination of two or more.

[0089] The type of the acid anhydride group-containing compound of the component (x3) is not particularly limited as long as it can react with the component (x2) to form an imide structure (preferably a cyclic imide structure).As the acid anhydride group-containing compound, tetracarboxylic dianhydride is preferably used, and examples thereof include pyromellitic dianhydride, benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic anhydride, p-phenylene bis(trimellitate anhydride), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, cyclobutane tetracarboxylic anhydride, cyclopentane tetracarboxylic anhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, and 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione. The component (x3) may be used alone or in combination of two or more.

[0090] As for the (x4) component, suitable examples of the oligophenylene ether skeleton are as described above. As the (x4) component, any polyol compound containing an oligophenylene ether skeleton may be used depending on the structure of the target resin X (i.e., the oligophenylene ether skeleton). For example, an example of a polyol compound containing an oligophenylene ether skeleton represented by the above formula (2-1) is "NORYL SA90" manufactured by Sabic. As the (x4) component, depending on the type of oligophenylene ether skeleton contained in the resin X, one type may be used alone, or two or more types may be used in combination.

[0091] The synthesis reaction of resin X using these (x1) to (x4) components may be carried out according to the conditions usually adopted in the imidization reaction using a polyol compound, an isocyanate compound, and an acid anhydride group-containing compound, and the reaction raw materials including the (x1) to (x4) components may be reacted all at once, or the (x1) to (x4) components may be reacted sequentially. When the reaction raw materials including the (x1) to (x4) components are reacted all at once, the reaction temperature may be, for example, in the range of 100 to 160°C, and the reaction time may be, for example, in the range of 4 to 10 hours. When the (x1) to (x4) components are reacted sequentially, the (x1) component and the (x2) component may be reacted, for example, in the range of 50 to 100°C for 0.5 to 4 hours, and then the (x3) component and the (x4) component may be added and reacted, for example, in the range of 120 to 160°C for 3 to 6 hours.

[0092] In the reaction of the components (x1) to (x4), a catalyst may be used, for example, tertiary amines such as tetramethylbutanediamine, benzyldimethylamine, triethanolamine, triethylamine, N,N'-dimethylpiperidine, α-methylbenzyldimethylamine, N-methylmorpholine, and triethylenediamine, and organometallic catalysts such as dibutyltin laurate, dimethyltin dichloride, cobalt naphthenate, and zinc naphthenate.

[0093] In such a reaction, by changing the degree of reaction between the (x1) component and the (x2) component or the ratio of the (x1) component to the (x4) component, it is possible to adjust the molecular weight of the resin X, the proportion of the flexible skeleton in the resin X, and ultimately the glass transition temperature of the resin X.

[0094] From the viewpoint of obtaining a cured product having good folding resistance and insulation reliability as well as good heat resistance (substrate adhesion after reflow), the mass ratio of resin X to inorganic filler (resin X / inorganic filler) is preferably 0.3 or more, more preferably 0.5 or more, even more preferably 0.6 or more, 0.8 or more, 1 or more, more than 1, 1.1 or more, or 1.2 or more. In particular, when the mass ratio of resin X / inorganic filler is more than 1, it is preferable that a cured product having excellent folding resistance, insulation reliability, and heat resistance is easily obtained. From the same viewpoint, the upper limit of the mass ratio is preferably 3 or less, more preferably 2.5 or less, even more preferably 2 or less, 1.8 or less, 1.6 or less, or 1.5 or less.

[0095] From the viewpoint of enjoying the effects of the present invention, the content of resin X in the resin composition is preferably 20% by mass or more, more preferably 25% by mass or more, even more preferably 30% by mass or more, even more preferably 35% by mass or more, 40% by mass or more, or 45% by mass or more, particularly preferably 50% by mass or more, 55% by mass or more, or 60% by mass or more, and the upper limit is preferably less than 85% by mass, 84% by mass or less, or 82% by mass or less, more preferably 80% by mass or less, or less than 80% by mass. Therefore, in one embodiment, when the resin component in the resin composition is 100% by mass, the content of resin X is 20% by mass or more and less than 85% by mass.

[0096] <Hardening agent> The resin composition of the present invention may further contain a curing agent.

[0097] The curing agent is not particularly limited, but examples thereof include active ester curing agents, phenol curing agents, naphthol curing agents, carbodiimide curing agents, acid anhydride curing agents, amine curing agents, benzoxazine curing agents, cyanate ester curing agents, and thiol curing agents. The curing agent may be used alone or in combination of two or more. From the viewpoint of being able to enjoy the effects of the present invention, it is preferable that the curing agent is one or more selected from active ester curing agents, phenol curing agents, and carbodiimide curing agents.

[0098] As the active ester curing agent, a compound having one or more active ester groups in one molecule can be used. Among them, as the active ester curing agent, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferable. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent derived from a carboxylic acid compound is preferable, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is more preferable, and an active ester curing agent obtained from a carboxylic acid compound and an aromatic hydroxy compound is even more preferable.

[0099] The carboxylic acid compound may be either an aromatic carboxylic acid compound or an aliphatic carboxylic acid compound, and examples thereof include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, and halides thereof.

[0100] Examples of aromatic hydroxy compounds include (i) polyaddition products of unsaturated aliphatic cyclic compounds containing two double bonds in one molecule and phenols, (ii) various bisphenol compounds, (iii) aromatic polyols having two or more hydroxyl groups bonded to the carbon atoms on the aromatic ring, and (iv) aromatic monools having one hydroxyl group bonded to the carbon atoms on the aromatic ring. Examples of polyaddition products of unsaturated aliphatic cyclic compounds and phenols include polyaddition products of unsaturated aliphatic cyclic compounds such as dicyclopentadiene, tetrahydroindene, norbornadiene, limonene, and vinylcyclohexene with phenols that may have a substituent (e.g., phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halophenol, etc.), and specifically, for example, dicyclopentadiene-phenols polyaddition products. Examples of bisphenol compounds include bisphenol A, bisphenol F, bisphenol AF, bisphenol AP, bisphenol B, bisphenol BP, bisphenol C, and bisphenol M. Examples of aromatic polyols having two or more hydroxy groups bonded to carbon atoms on an aromatic ring include hydroquinone, resorcinol, catechol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, benzenetriol, and phenol novolak. Examples of aromatic monools having one hydroxy group bonded to a carbon atom on an aromatic ring include phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halophenol, naphthol, methylnaphthol, dimethylnaphthol, ethylnaphthol, propylnaphthol, vinylnaphthol, allylnaphthol, phenylnaphthol, benzylnaphthol, and halonaphthol.

[0101] Suitable specific examples of the active ester curing agent include an active ester compound containing a dicyclopentadiene-type diphenol structure, an active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of phenol novolac, and an active ester compound containing a benzoylated product of phenol novolac. Among them, an active ester compound containing a naphthalene structure and an active ester compound containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentalene-phenylene.

[0102] Commercially available active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); and active ester compounds containing a naphthalene structure, such as "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", and "HPC-8150-62T". and "EXB-8" (manufactured by DIC Corporation); an active ester compound containing phosphorus, "EXB9401" (manufactured by DIC Corporation), an active ester compound which is an acetylated product of phenol novolac, "DC808" (manufactured by Mitsubishi Chemical Corporation), active ester compounds which are benzoylated products of phenol novolac, "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester compound containing a styryl group and a naphthalene structure, "PC1300-02-65MA" (manufactured by Air Water Corporation), etc.

[0103] As the phenol-based curing agent and naphthol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure or a naphthol-based curing agent having a novolac structure is preferred. Also, from the viewpoint of achieving an insulating layer having good adhesion strength (peel strength) with a conductor layer, a nitrogen-containing phenol-based curing agent or a nitrogen-containing naphthol-based curing agent is preferred, and a triazine skeleton-containing phenol-based curing agent or a triazine skeleton-containing naphthol-based curing agent is more preferred. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion strength with a conductor layer, a triazine skeleton-containing phenol novolac resin or a triazine skeleton-containing naphthol novolac resin is preferred.

[0104] Specific examples of phenol-based curing agents and naphthol-based curing agents include, for example, "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Chemical Industry Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; and "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", and "SN-37" manufactured by Nippon Steel Chemical & Material Co., Ltd. 5" and "SN-395" manufactured by DIC Corporation; "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", and "KA-1165" manufactured by Gun-ei Chemical Co., Ltd.; and the like.

[0105] Examples of the carbodiimide-based curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, such as aliphatic biscarbodiimides, such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides, such as phenylene-bis(xylylcarbodiimide); and aliphatic polycarbodiimides, such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide). ; polycarbodiimides such as aromatic polycarbodiimides such as poly(phenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide].

[0106] Commercially available carbodiimide curing agents include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie.

[0107] Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule, and a curing agent having two or more acid anhydride groups in one molecule is preferable. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and the like. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd., and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Clay Valley.

[0108] The amine-based curing agent may be a curing agent having one or more, preferably two or more, amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or secondary amine, more preferably a primary amine. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. As the amine-based curing agent, commercially available products may be used, and examples thereof include "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.

[0109] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation; "HFB2006M" manufactured by Showa Polymer Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0110] Examples of cyanate ester curing agents include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0111] Examples of thiol-based curing agents include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.

[0112] The reactive group equivalent of the curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the curing agent per equivalent of the reactive group.

[0113] From the viewpoint of easily realizing a cured product with a low dielectric tangent, the curing agent preferably contains an active ester curing agent. When the curing agent contains an active ester curing agent, when the non-volatile components in the curing agent are taken as 100% by mass, the content of the active ester curing agent is preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more or 50% by mass or more, and the upper limit may be 100% by mass, but may also be, for example, 98% by mass or less, 95% by mass or less, or 90% by mass or less.

[0114] When the resin composition of the present invention contains a curing agent, the content of the curing agent in the resin composition is not particularly limited, but is preferably 1% by mass or more, more preferably 3% by mass or more, further preferably 5% by mass or more, 6% by mass or more, or 7% by mass or more, when the resin component in the resin composition is 100% by mass. The upper limit of the content of the curing agent is preferably 50% by mass or less, more preferably 40% by mass or less, 35% by mass or less, 30% by mass or less, or 25% by mass or less.

[0115] <Curing accelerator> The resin composition of the present invention may further contain a curing accelerator. By containing a curing accelerator, the curing time and the curing temperature can be efficiently adjusted.

[0116] Examples of the curing accelerator include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. From the viewpoint of obtaining the effects of the present invention, the curing accelerator preferably contains an amine-based curing accelerator or an imidazole-based curing accelerator, and more preferably contains an imidazole-based curing accelerator. The curing accelerator may be used alone or in combination of two or more.

[0117] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hydrogenhexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate ... aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0118] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0119] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0120] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct imidazole compounds such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins.

[0121] As the imidazole-based curing accelerator, commercially available products may be used, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2P4MZ", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; "P200-H50" manufactured by Mitsubishi Chemical Corporation, etc. These may be used alone or in combination of two or more kinds.

[0122] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0123] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine (DMAP), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0124] When the resin composition of the present invention contains a curing accelerator, the content of the curing accelerator in the resin composition is not particularly limited, but when the resin component in the resin composition is taken as 100 mass%, it is preferably 0.01 mass% or more, more preferably 0.03 mass% or more, and even more preferably 0.05 mass% or more, and the upper limit is preferably 3 mass% or less, more preferably 2 mass% or less, 1.5 mass% or less, or 1 mass% or less.

[0125] <Compound having a radically polymerizable unsaturated group> The resin composition of the present invention may contain a compound having a radically polymerizable unsaturated group as an optional component. By containing a compound having a radically polymerizable unsaturated group, it is preferable to easily realize a resin composition that provides a cured product having better folding resistance and insulation reliability, and also better heat resistance characteristics (adhesion to the substrate after reflow).

[0126] The compound having a radically polymerizable unsaturated group may be used alone or in combination of two or more kinds.

[0127] The type of the compound having a radical polymerizable unsaturated group is not particularly limited, as long as it has one or more (preferably two or more) radical polymerizable unsaturated groups in one molecule. Examples of the compound containing a radical polymerizable unsaturated group include compounds having one or more radical polymerizable unsaturated groups selected from maleimide groups, vinyl groups, allyl groups, styryl groups, vinylphenyl groups, acryloyl groups, methacryloyl groups, fumaroyl groups, and maleoyl groups. Among them, from the viewpoint of easily realizing a resin composition that exhibits better folding resistance and insulation reliability and also provides a cured product with better heat resistance characteristics (substrate adhesion after reflow), it is preferable to include one or more selected from maleimide compounds, allyl compounds, styryl compounds, and (meth)acrylic compounds.

[0128] The type of maleimide compound is not particularly limited as long as it has one or more (preferably two or more) maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl groups) in one molecule. Examples of the maleimide compound include (1) "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", and "BMI-689" (all manufactured by Designer Molecules), "SLK-6895", and "SLK-1500" (manufactured by Shin-Etsu Chemical Co., Ltd.), which have an aliphatic skeleton (a divalent aliphatic group having 10 or more carbon atoms, particularly preferably derived from a dimer acid or dimer diamine). (2) maleimide compounds containing an indane skeleton, as described in the Technical Journal Disclosure No. 2020-500211 of the Japan Institute of Invention and Innovation; and (3) maleimide compounds containing an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group, such as "MIR-3000-70MT" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000" (manufactured by Daiwa Kasei Co., Ltd.), and "BMI-80" (manufactured by Keiai Kasei Co., Ltd.).

[0129] The allyl compound is not particularly limited in type, so long as it has one or more (preferably two or more) allyl groups in one molecule, and may be a monomer or an oligomer. Examples of the allyl compound include aromatic carboxylic acid allyl ester compounds such as diallyl diphenate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl 2,6-naphthalenedicarboxylate, and diallyl 2,3-naphthalenecarboxylate; isocyanuric acid allyl ester compounds such as 1,3,5-triallyl isocyanurate and 1,3-diallyl-5-glycidyl isocyanurate; epoxy-containing aromatic allyl compounds such as 2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane; benzoxazine-containing aromatic allyl compounds such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane; ether-containing aromatic allyl compounds such as 1,3,5-triallyl ether benzene; allyl silane compounds such as diallyl diphenyl silane; and resins containing a plurality of benzene rings and allyl groups. Commercially available allyl compounds include, for example, Meiwa Kasei's "MEH-8000H" and "MEH-8005" (allyl resin having a phenol ring); Shikoku Kasei Corporation's "ALP-d" (allyl resin having a benzoxazine ring); Shikoku Kasei Corporation's "L-DAIC" (allyl resin having an isocyanuric ring); Nippon Kasei's "TAIC" (allyl resin having an isocyanuric ring (triallyl isocyanurate)); Osaka Soda's "MDAC" (allyl resin having a cyclohexanedicarboxylic acid derivative); Nisshoku Techno Fine Chemical's "DAD" (diallyl diphenate); and Osaka Soda's "Daiso DAP Monomer" (ortho-diallyl phthalate).

[0130] The styryl compound is not particularly limited in type, and may be a monomer or oligomer, as long as it has one or more (preferably two or more) styryl groups or vinylphenyl groups in one molecule. Examples of the styryl compound include low molecular weight (molecular weight less than 1000) styryl compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl)ether; and high molecular weight (molecular weight 1000 or more) styryl compounds such as vinylbenzyl-modified polyphenylene ether resin and styrene-divinylbenzene copolymer. Commercially available styryl compounds include, for example, "ODV-XET(X03)", "ODV-XET(X04)", and "ODV-XET(X05)" (styrene-divinylbenzene copolymers) manufactured by Nippon Steel Chemical & Material Co., Ltd., and "OPE-2St 1200" and "OPE-2St 2200" (vinylbenzyl-modified polyphenylene ether resins) manufactured by Mitsubishi Gas Chemical Co., Inc.

[0131] The (meth)acrylic compound is not particularly limited in type as long as it has one or more (preferably two or more) (meth)acryloyl groups in one molecule, and may be a monomer or oligomer (excluding compounds corresponding to component (C)). Examples of the (meth)acrylic compound include cyclohexane-1,4-dimethanol di(meth)acrylate, cyclohexane-1,3-dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and the like. (meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and other low molecular weight (molecular weight less than 1000) aliphatic (meth)acrylic acid ester compounds; dioxane glycol di(meth)acrylate, 3,6-dioxa-1,8-octanediol di(meth)acrylate, acrylate, 3,6,9-trioxaundecane-1,11-diol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, and other low molecular weight (molecular weight less than 1000) ether-containing (meth)acrylic acid ester compounds; tris(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and other low molecular weight (molecular weight less than 1000) isocyanurate-containing (meth)acrylic acid ester compounds; and high molecular weight (molecular weight 1000 or more) acrylic acid ester compounds such as (meth)acrylic modified polyphenylene ether resins. Examples of commercially available (meth)acrylic compounds include "A-DOG" (dioxane glycol diacrylate) manufactured by Shin-Nakamura Chemical Co., Ltd., "DCP-A" (tricyclodecane dimethanol diacrylate) and "DCP" (tricyclodecane dimethanol dimethacrylate) manufactured by Kyoeisha Chemical Co., Ltd., "KAYARAD R-684" (tricyclodecane dimethanol diacrylate) and "KAYARAD R-604" (dioxane glycol diacrylate) manufactured by Nippon Kayaku Co., Ltd., and "SA9000" and "SA9000-111" (methacrylic-modified polyphenylene ether) manufactured by SABIC Innovative Plastics.

[0132] The radical polymerizable unsaturated group equivalent of the compound having a radical polymerizable unsaturated group is preferably 250 g / eq. to 1200 g / eq., more preferably 300 g / eq. to 1100 g / eq. The radical polymerizable unsaturated group equivalent represents the mass of the compound having a radical polymerizable unsaturated group per equivalent of the radical polymerizable unsaturated group. When the radical polymerizable unsaturated group equivalent of the compound having a radical polymerizable unsaturated group is within the above range, the effect of the present invention can be significantly obtained.

[0133] The Mw of the compound having a radically polymerizable unsaturated group is preferably 1000 to 40000, and more preferably 1500 to 35000. The Mw of the compound having a radically polymerizable unsaturated group can be measured by a GPC method as a polystyrene-equivalent value.

[0134] When the resin composition of the present invention contains a compound having a radical polymerizable unsaturated group, the content of the compound having a radical polymerizable unsaturated group in the resin composition is, from the viewpoint of better enjoying the effects of the present invention, preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 1.5% by mass or more, 2% by mass or more, or 2.5% by mass or more, when the resin component in the resin composition is taken as 100% by mass, and the upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less, 15% by mass or less, 14% by mass or less, 12% by mass or less, or 10% by mass or less.

[0135] <Other additives> The resin composition of the present invention may further contain any additive as a non-volatile component. Examples of such additives include organic fillers such as rubber particles, polyamide fine particles, and silicone particles; thermoplastic resins such as polycarbonate resins, phenoxy resins, polyvinyl acetal resins, polyolefin resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polyether ether ketone resins, and polyester resins; radical polymerization initiators such as peroxide-based radical polymerization initiators and azo-based radical polymerization initiators; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; silicone-based leveling agents, acrylic polymer-based leveling agents, and the like. Examples of the additives include leveling agents such as leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone defoamers, acrylic defoamers, fluorine defoamers, and vinyl resin defoamers; ultraviolet absorbers such as benzotriazole ultraviolet absorbers; adhesion improvers such as urea silane; adhesion imparters such as triazole adhesion imparters, tetrazole adhesion imparters, and triazine adhesion imparters; antioxidants such as hindered phenol antioxidants and hindered amine antioxidants; fluorescent brighteners such as stilbene derivatives; surfactants such as fluorine surfactants and silicone surfactants; flame retardants other than non-reactive phosphazene compounds such as phosphorus flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen flame retardants (e.g., melamine sulfate), halogen flame retardants, and inorganic flame retardants (e.g., antimony trioxide). The additives may be used alone or in combination of two or more in any ratio. The contents of other additives can be appropriately determined by those skilled in the art.

[0136] <Organic solvent> The resin composition of the present invention may further contain an arbitrary organic solvent as a volatile component in addition to the non-volatile components described above. As the organic solvent, a known one can be appropriately used, and the type is not particularly limited. Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, and diphenyl ether; alcohol-based solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, and methyl methoxypropionate. Examples of the organic solvent include ether ester solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The organic solvent may be used alone or in combination of two or more in any ratio.

[0137] The resin composition of the present invention can be produced, for example, by adding and mixing the oligophenylene ether skeleton-containing resin X, the thermosetting resin, the inorganic filler, and further, if necessary, the curing agent, the curing accelerator, the compound having a radically polymerizable unsaturated group, other additives, and the organic solvent in any order and / or all at once in any order into any reaction vessel. In addition, the temperature can be appropriately set during the process of adding and mixing each component, and heating and / or cooling may be performed temporarily or throughout. In addition, stirring or shaking may be performed during the process of adding and mixing each component. In addition, during or after adding and mixing, the resin composition may be stirred using a stirring device such as a mixer to disperse uniformly.

[0138] The resin composition of the present invention contains a thermosetting resin, an inorganic filler, and an oligophenylene ether skeleton-containing resin X having a glass transition temperature of 25° C. or lower, and a cured product thereof exhibits a dielectric loss tangent Df of less than 0.01 and satisfies the following conditions (1) and (2): (1) Elongation is 5% or more but less than 50% (2) MIT folding endurance test: 200 or more folding cycles According to such a resin composition, it is possible to obtain a cured product having good folding endurance and insulation reliability, as well as good heat resistance (adhesion to the base after reflow).

[0139] From the viewpoint of providing a cured product having good folding resistance and insulation reliability as well as good heat resistance (adhesion to substrate after reflow), it is important that the cured product of the resin composition of the present invention has a dielectric loss tangent Df of less than 0.01. For example, as described in the <Measurement of Dielectric Loss Tangent> section below, when measured at 5.8 GHz and 23°C, the dielectric loss tangent Df of the cured product of the resin composition of the present invention is less than 0.01, and is preferably 0.009 or less, 0.008 or less, or 0.007 or less.

[0140] In order to provide a cured product that exhibits good folding endurance and insulation reliability as well as good heat resistance (adhesion to the substrate after reflow), the cured product of the resin composition of the present invention satisfies the following conditions (1) and (2): (1) An elongation of 5% or more and less than 50% (2) The number of folding endurance in the MIT folding endurance test is 200 or more It is important to satisfy at least one of the above.

[0141] Regarding the above condition (1) in detail, the cured product of the resin composition of the present invention preferably has an elongation rate (elongation at break) measured by the method described in the <Elongation Evaluation> column described later of 5% or more and less than 50%. The lower limit is preferably 6% or more, more preferably 8% or more, still more preferably 10% or more, and the upper limit is preferably 45% or less, more preferably 40% or less, still more preferably 35% or less or 30% or less.

[0142] Regarding the above condition (2) in detail, the cured product of the resin composition of the present invention preferably has a number of folding endurance measured by the method described in the <MIT Test Folding Endurance Evaluation> column described later of 200 or more. Preferably 220 or more, more preferably 240 or more, still more preferably 250 or more, 260 or more, 280 or more, or 300 or more. The upper limit of the number of folding endurance is not particularly limited, and may be, for example, 2000 or less, 1500 or less, 1000 or less, etc.

[0143] The cured product of the resin composition of the present invention is characterized by exhibiting good insulation reliability. The cured product of the resin composition of the present invention preferably has an insulation resistance value after exposure to a high-temperature and high-humidity environment (with a bias voltage applied) measured by the method described in the <Insulation Reliability Evaluation> column described later of 1.00×10 8 Ω or more, more preferably 5.00×10 8 Ω or more, still more preferably 1.00×10 9 Ω or more.

[0144] The cured product of the resin composition of the present invention is characterized by exhibiting good heat resistance (conductor adhesion after reflow). For example, as described in the <Evaluation of adhesion to substrate> section below, the cured product of the resin composition of the present invention has a peel strength after reflow measured in accordance with JIS C6481 of preferably 0.4 kgf / cm or more, more preferably 0.45 kgf / cm or more, even more preferably 0.5 kgf / cm or more, 0.55 kgf / cm or more, 0.6 kgf / cm or more, 0.65 kgf / cm or more, or 0.7 kgf / cm or more.

[0145] The resin composition of the present invention can provide a cured product that exhibits good folding resistance and insulation reliability, and also has good heat resistance (substrate adhesion after reflow). Therefore, the resin composition of the present invention can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for insulating layer of printed wiring board), and more suitably used as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for interlayer insulating layer of printed wiring board). Among them, it can be suitably used as a resin composition for forming an insulating layer of a flexible printed wiring board (flexible substrate) (resin composition for insulating layer of flexible substrate), and more suitably used as a resin composition for forming an interlayer insulating layer of a flexible substrate (resin composition for interlayer insulating layer of flexible substrate). The resin composition of the present invention can also be used in a wide range of applications such as solder resist, underfill material, die bonding material, semiconductor encapsulation material, hole filling resin, and component embedding resin.

[0146] [Sheet-type laminated materials (resin sheets, prepregs)] The resin composition of the present invention can be used as it is, but it may also be used in the form of a sheet-like laminate material containing the resin composition.

[0147] As the sheet-like laminate material, the following resin sheets and prepregs are preferred.

[0148] In one embodiment, the resin sheet includes a support and a layer of a resin composition (hereinafter simply referred to as a "resin composition layer") provided on the support, and is characterized in that the resin composition layer is formed from the resin composition of the present invention.

[0149] The thickness of the resin composition layer may vary depending on the application, and may be appropriately determined depending on the application. For example, the thickness of the resin composition layer is preferably 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less from the viewpoint of thinning the flexible printed wiring board. The lower limit of the thickness of the resin composition layer is not particularly limited, but may usually be 1 μm or more, 5 μm or more, etc.

[0150] Examples of the support include a thermoplastic resin film, a metal foil, and a release paper, and a thermoplastic resin film and a metal foil are preferred. Thus, in a preferred embodiment, the support is a thermoplastic resin film or a metal foil.

[0151] When a thermoplastic resin film is used as the support, examples of the thermoplastic resin include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylics such as polycarbonate (PC) and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0152] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0153] The support may be subjected to a matte treatment, a corona treatment, or an antistatic treatment on the surface to be bonded to the resin composition layer. In addition, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used as the support. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0154] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0155] When a metal foil is used as the support, a metal foil with a support substrate may be used, which is a thin metal foil with a peelable support substrate attached thereto. In one embodiment, the metal foil with a support substrate includes a support substrate, a release layer provided on the support substrate, and a metal foil provided on the release layer. When a metal foil with a support substrate is used as the support, the resin composition layer is provided on the metal foil.

[0156] In the metal foil with a supporting substrate, the material of the supporting substrate is not particularly limited, and examples thereof include copper foil, aluminum foil, stainless steel foil, titanium foil, copper alloy foil, etc. When copper foil is used as the supporting substrate, it may be electrolytic copper foil or rolled copper foil. In addition, the release layer is not particularly limited as long as it can release the metal foil from the supporting substrate, and examples thereof include an alloy layer of an element selected from the group consisting of Cr, Ni, Co, Fe, Mo, Ti, W, and P; an organic coating, etc.

[0157] In the metal foil with a supporting substrate, the material of the metal foil is preferably, for example, copper foil or copper alloy foil.

[0158] In the metal foil with a supporting substrate, the thickness of the supporting substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, more preferably in the range of 10 μm to 100 μm, and the thickness of the metal foil may be, for example, in the range of 0.1 μm to 10 μm.

[0159] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and the like to the surface of the resin composition layer and scratches.

[0160] The resin sheet can be produced, for example, by preparing a liquid resin composition as is or a resin varnish by dissolving the resin composition in an organic solvent, applying this onto a support using a die coater or the like, and then drying to form a resin composition layer.

[0161] The organic solvent may be the same as the organic solvent described as a component of the resin composition. The organic solvent may be used alone or in combination of two or more kinds.

[0162] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of the organic solvent in the resin composition layer becomes 10% by mass or less, preferably 5% by mass or less. Although it varies depending on the boiling point of the organic solvent in the resin composition or resin varnish, for example, when a resin composition or resin varnish containing 30% by mass to 60% by mass of the organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0163] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0164] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber substrate with the resin composition of the present invention.

[0165] The sheet-like fiber substrate used for the prepreg is not particularly limited, and can be a substrate commonly used for prepreg, such as glass cloth, aramid nonwoven fabric, or liquid crystal polymer nonwoven fabric. From the viewpoint of thinning of printed wiring boards and semiconductor chip packages, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.

[0166] The prepreg can be produced by a known method such as a hot melt method or a solvent method.

[0167] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.

[0168] The sheet-like laminate material of the present invention can be suitably used to form an insulating layer of a printed wiring board (for insulating layer of a printed wiring board), and can be more suitably used to form an interlayer insulating layer of a printed wiring board (for interlayer insulating layer of a printed wiring board). In particular, it can be suitably used to form an insulating layer of a flexible substrate (for insulating layer of a flexible substrate), and can be more suitably used to form an interlayer insulating layer of a flexible substrate (for interlayer insulating layer of a flexible substrate).

[0169] [Laminated sheet] The laminate sheet is a sheet produced by laminating and curing a plurality of resin composition layers.

[0170] The laminate sheet includes a plurality of insulating layers as cured products of the resin composition layers. Usually, the number of resin composition layers laminated to produce the laminate sheet corresponds to the number of insulating layers included in the laminate sheet. The specific number of insulating layers per laminate sheet is usually 2 or more, preferably 3 or more, particularly preferably 5 or more, and preferably 20 or less, more preferably 15 or less, particularly preferably 10 or less.

[0171] The laminate sheet is a sheet that is folded so that one side of the laminate sheet faces the other when used. The minimum bending radius of the laminate sheet is not particularly limited, but is preferably 0.1 mm or more, more preferably 0.2 mm or more, and even more preferably 0.3 mm or more, and is preferably 5 mm or less, more preferably 4 mm or less, and particularly preferably 3 mm or less.

[0172] Each insulating layer included in the laminated sheet may have a hole formed therein, which can function as a via hole or a through hole in the flexible substrate.

[0173] The laminated sheet may further include an optional element in addition to the insulating layer. For example, the laminated sheet may include a conductor layer as an optional element. The conductor layer is usually partially formed on the surface of the insulating layer or between the insulating layers. This conductor layer usually functions as wiring in the flexible substrate.

[0174] The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor material may be a single metal or an alloy. Examples of the alloy include alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among them, from the viewpoints of versatility of conductor layer formation, cost, ease of patterning, etc., single metals such as chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper; and alloys such as nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy; are preferred. Among them, single metals such as chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper; and nickel-chromium alloy; are more preferred, and single metal copper is even more preferred.

[0175] The conductor layer may be a single-layer structure or a multi-layer structure including two or more single metal layers or alloy layers made of different kinds of metals or alloys. When the conductor layer is a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0176] The conductor layer may be patterned to function as wiring.

[0177] The thickness of the conductor layer depends on the design of the flexible substrate, but is preferably 3 μm to 35 μm, more preferably 5 μm to 30 μm, further preferably 10 μm to 20 μm, and particularly preferably 15 μm to 20 μm.

[0178] The thickness of the laminate sheet is preferably 100 μm or more, more preferably 150 μm or more, and even more preferably 200 μm or more, and is preferably 2,000 μm or less, more preferably 1,000 μm or less, and even more preferably 500 μm or less.

[0179] <Method of manufacturing laminated sheet> The laminate sheet can be produced by a method including the steps of (a) preparing a resin sheet, and (b) laminating and curing a plurality of resin composition layers using the resin sheet.

[0180] The order of lamination and curing of the resin composition layers is arbitrary as long as the desired laminated sheet is obtained. For example, after laminating all of the resin composition layers, the laminated resin composition layers may be cured all at once depending on the components contained in the resin composition. In addition, for example, each time a resin composition layer is laminated on a resin composition layer, the laminated resin composition layer may be cured.

[0181] A preferred embodiment of step (b) will be described below. In the embodiment described below, for the purpose of distinction, the resin composition layers are appropriately numbered and shown as "first resin composition layer" and "second resin composition layer", and the insulating layers obtained by curing these resin composition layers are also numbered and shown as "first insulating layer" and "second insulating layer" in the same manner as the resin composition layers.

[0182] In a preferred embodiment, step (b) comprises: (II) curing the first resin composition layer to form a first insulating layer; (VI) laminating a second resin composition layer on the first insulating layer; (VII) curing the second resin composition layer to form a second insulating layer; Includes.

[0183] In addition, step (b) may include, as necessary: (I) laminating a first resin composition layer onto a sheet supporting substrate; (III) drilling holes in the first insulating layer; (IV) subjecting the first insulating layer to a roughening treatment; (V) forming a conductor layer on the first insulating layer Each step will be described below.

[0184] Step (I) is a step of laminating a first resin composition layer onto a sheet supporting substrate prior to step (II). The sheet supporting substrate is a peelable member, and for example, a plate-, sheet- or film-shaped member is used.

[0185] The lamination of the sheet support substrate and the first resin composition layer may be performed by a vacuum lamination method. In the vacuum lamination method, the heat-pressure bonding temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heat-pressure bonding pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the heat-pressure bonding time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably performed under reduced pressure conditions of 26.7hPa or less.

[0186] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0187] When a resin sheet is used, the lamination of the sheet support substrate and the first resin composition layer can be performed, for example, by pressing the resin sheet from the support side and thermocompressing the first resin composition layer of the resin sheet to the sheet support substrate. Examples of the member for thermocompressing the resin sheet to the sheet support substrate (hereinafter, also referred to as "thermocompression member") include a heated metal plate (SUS mirror plate, etc.) or a metal roll (SUS roll), etc. It is preferable to press the thermocompression member through an elastic material such as heat-resistant rubber so that the first resin composition layer sufficiently follows the surface irregularities of the sheet support substrate, rather than directly pressing the resin sheet with the thermocompression member.

[0188] After lamination, the first resin composition layer may be smoothed by pressing, for example, with a heat-pressure bonding member under normal pressure (atmospheric pressure). For example, when a resin sheet is used, the first resin composition layer of the resin sheet can be smoothed by pressing the resin sheet from the support side with a heat-pressure bonding member. The pressing conditions for the smoothing treatment can be the same as the heat-pressure bonding conditions for the lamination. The smoothing treatment can be performed with a commercially available laminator. The lamination and the smoothing treatment may be performed continuously using the commercially available vacuum laminator.

[0189] Step (II) is a step of curing the first resin composition layer to form a first insulating layer. The curing conditions of the first resin composition layer are not particularly limited, and the conditions adopted when forming an insulating layer of a printed wiring board can be applied arbitrarily. The first resin composition layer can be cured by drying, but when it contains a thermosetting resin such as an epoxy resin, it can be cured by drying and then thermally curing.

[0190] Specific heat curing conditions vary depending on the type of resin composition. For example, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 110 minutes, and even more preferably 20 minutes to 100 minutes.

[0191] Before the first resin composition layer is thermally cured, the first resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the first resin composition layer, the first resin composition layer may be preheated for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes) at a temperature of 50°C or more and less than 120°C (preferably 60°C or more and 115°C or less, and more preferably 70°C or more and 110°C or less).

[0192] Step (III) is a step of drilling holes in the first insulating layer. This step (III) allows holes such as via holes and through holes to be formed in the first insulating layer. The holes may be drilled using, for example, a drill, a laser, plasma, or the like, depending on the composition of the resin composition. The dimensions and shape of the holes may be appropriately set depending on the design of the flexible substrate.

[0193] Step (IV) is a step of performing a roughening treatment on the first insulating layer. Usually, in this step (IV), smears are also removed. Therefore, the roughening treatment is sometimes called a desmear treatment. An example of the roughening treatment is a method in which a swelling treatment using a swelling liquid, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing liquid are performed in this order.

[0194] The swelling liquid is not particularly limited, and examples thereof include alkaline aqueous solutions such as an aqueous sodium hydroxide solution and an aqueous potassium hydroxide solution. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid can be carried out, for example, by immersing the cured body in the swelling liquid at 30 to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in the swelling liquid at 40 to 80°C for 5 to 15 minutes.

[0195] The oxidizing agent is not particularly limited, but examples thereof include an alkaline permanganate solution in which a permanganate is dissolved in an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution. The concentration of the permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact P", "Concentrate Compact CP", and "Dosing Solution Securigans P" manufactured by Atotech Japan. The roughening treatment using an oxidizing agent can be performed by immersing the cured body in an oxidizing agent solution heated to 60°C to 80°C for 10 minutes to 30 minutes.

[0196] An acidic aqueous solution is used as the neutralizing liquid. An example of a commercially available product is "Reduction Solution Securigant P" manufactured by Atotech Japan. The treatment with the neutralizing liquid can be carried out by immersing the hardened body in the neutralizing liquid at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., it is preferable to immerse the hardened body in the neutralizing liquid at 40°C to 70°C for 5 to 20 minutes.

[0197] The arithmetic mean roughness (Ra) of the surface of the first insulating layer after the roughening treatment is preferably 400 nm or less, more preferably 300 nm or less, and even more preferably 200 nm or less. The lower limit is not particularly limited, but may be 30 nm or more, 40 nm or more, or 50 nm or more.

[0198] Step (V) is a step of forming a conductor layer on the first insulating layer as necessary. The conductor layer can be formed by, for example, plating, sputtering, vapor deposition, etc., among which plating is preferred. A suitable example is a method of plating the surface of the first insulating layer by an appropriate method such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. Among these, the semi-additive method is preferred from the viewpoint of ease of production.

[0199] An example of forming a conductor layer by a semi-additive method is shown below. First, a plating seed layer is formed on the surface of a first insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by a process such as etching to form a conductor layer having a desired wiring pattern.

[0200] A first insulating layer is obtained in step (II), and step (III), step (IV), and step (V) are performed as necessary, followed by step (VI). Step (VI) is a step of laminating a second resin composition layer on the first insulating layer. The lamination of the first insulating layer and the second resin composition layer can be performed in the same manner as the lamination of the sheet support substrate and the first resin composition layer in step (I).

[0201] However, when the first resin composition layer is formed using a resin sheet, the support of the resin sheet is removed prior to step (VI). The removal of the support may be performed between step (I) and step (II), between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V).

[0202] After step (VI), step (VII) is performed. Step (VII) is a step of curing the second resin composition layer to form a second insulating layer. The second resin composition layer can be cured by the same method as the curing of the first resin composition layer in step (II). This makes it possible to obtain a laminate sheet including a plurality of insulating layers, namely, a first insulating layer and a second insulating layer.

[0203] In addition, in the method according to the embodiment, the steps of (VIII) drilling holes in the second insulating layer, (IX) roughening the second insulating layer, and (X) forming a conductor layer on the second insulating layer may be performed as necessary. The drilling of the second insulating layer in step (VIII) can be performed in the same manner as the drilling of the first insulating layer in step (III). The roughening of the second insulating layer in step (IX) can be performed in the same manner as the roughening of the first insulating layer in step (IV). Furthermore, the formation of the conductor layer on the second insulating layer in step (X) can be performed in the same manner as the formation of the conductor layer on the first insulating layer in step (V).

[0204] In the above embodiment, the laminate sheet is produced by laminating and curing two resin composition layers, a first resin composition layer and a second resin composition layer, but a laminate sheet may be produced by laminating and curing three or more resin composition layers. For example, in the method according to the above embodiment, the lamination and curing of the resin composition layers in steps (VI) to (VII), and, if necessary, the drilling of the insulating layer, the roughening treatment of the insulating layer, and the formation of a conductor layer on the insulating layer in steps (VIII) to (X) may be repeatedly carried out to produce a laminate sheet. This provides a laminate sheet including three or more insulating layers.

[0205] Furthermore, the method according to the embodiment may include any step other than the steps described above. For example, when step (I) is performed, a step of removing the sheet support substrate may be performed.

[0206] [Flexible PCB] Flexible substrates include a single-sided structure having a conductor layer on only one side of an insulating layer as a cured product of a resin composition, a double-sided structure having conductor layers on both sides of an insulating layer, and a multilayer structure (multilayer flexible substrate) in which insulating layers are stacked so that there are three or more conductor layers. The flexible substrate may include a laminate sheet. When a laminate sheet is included, the flexible substrate may include only the laminate sheet, or may include an optional member in combination with the laminate sheet. Examples of the optional member include electronic components, coverlay films, and the like.

[0207] The flexible substrate can be manufactured by a method including the steps of (a) preparing a resin sheet, or further including the steps of (b) laminating multiple resin composition layers using the resin sheet, and (c) curing the resin sheet or laminated sheet.

[0208] The manufacturing method of a flexible substrate may further include any step in combination with the above steps. For example, the manufacturing method of a flexible substrate having an electronic component may include a step of bonding the electronic component to a laminate sheet. The bonding conditions between the laminate sheet and the electronic component may be any condition that allows a conductive connection between the terminal electrodes of the electronic component and the conductor layer as wiring provided on the laminate sheet. Also, for example, the manufacturing method of a flexible substrate having a coverlay film may include a step of laminating the laminate sheet and the coverlay film.

[0209] The flexible substrate can be used by usually folding the laminated sheet included in the flexible substrate so that one side of the laminated sheet faces the other. For example, the flexible substrate is stored in a housing of a semiconductor device in a state where it is folded to reduce its size. Also, for example, the flexible substrate is provided on a movable part of a semiconductor device having a movable part that can be folded.

[0210] [Semiconductor Devices] The semiconductor device includes the flexible substrate. The semiconductor device includes, for example, a flexible substrate and a semiconductor chip mounted on the flexible substrate. In many semiconductor devices, the flexible substrate can be stored in the housing of the semiconductor device by folding the flexible substrate so that one side of the laminated sheet included in the flexible substrate faces the other side.

[0211] Examples of the semiconductor device include various semiconductor devices used in electrical appliances (such as computers, mobile phones, digital cameras, and televisions) and vehicles (such as motorcycles, automobiles, trains, ships, and aircraft).

[0212] The semiconductor device can be manufactured by a manufacturing method including, for example, a step of preparing a flexible substrate, a step of folding the flexible substrate so that one side of the laminated sheet faces the other, and a step of storing the folded flexible substrate in a housing. EXAMPLES

[0213] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" representing amounts means "parts by mass" unless otherwise specified.

[0214] <Synthesis Example 1: Synthesis of Resin X1> A reaction vessel was charged with 112 g of bifunctional hydroxyl-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3000, hydroxyl group equivalent = 1800 g / eq.), 272 g of anisole as a solvent, and 14 g of isophorone diisocyanate (IPDI), and the temperature was raised to 50°C to carry out the reaction for approximately 1 hour. Next, 145 g of oligophenylene ether resin containing phenolic hydroxyl groups at both ends ("SA90-100" manufactured by Sabic, hydroxyl group equivalent = 800 g / eq.) and 1 g of benzophenonetetracarboxylic dianhydride (BTDA) were added to the reaction mixture, and the mixture was heated to 140°C with stirring and reacted for about 4 hours. -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end of the reaction, and the reaction mixture was cooled to room temperature. The reaction mixture was then filtered through a 100-mesh filter cloth to obtain Resin X1 having an oligophenylene ether skeleton (non-volatile component 50% by mass, viscosity at 25°C 6.0 Pa s, weight-average molecular weight 280,000, glass transition temperature 0°C).

[0215] <Synthesis Example 2: Synthesis of Resin X2> A reaction vessel was charged with 60 g of bifunctional hydroxyl-terminated polybutadiene ("G-1000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 1400, hydroxyl group equivalent = 800 g / eq.), 220 g of anisole as a solvent, and 14 g of isophorone diisocyanate (IPDI), and the temperature was raised to 50°C to carry out the reaction for approximately 1 hour. Next, 145 g of oligophenylene ether resin containing phenolic hydroxyl groups at both ends ("SA90-100" manufactured by Sabic, hydroxyl group equivalent = 800 g / eq.) and 1 g of benzophenonetetracarboxylic dianhydride (BTDA) were added to the reaction mixture, and the mixture was heated to 140°C with stirring and reacted for about 4 hours. -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end of the reaction, and the reaction product was cooled to room temperature. The reaction product was then filtered through a 100-mesh filter cloth to obtain Resin X2 having an oligophenylene ether skeleton (non-volatile content 50% by mass, viscosity at 25°C 2.0 Pa s, weight-average molecular weight 260,000, glass transition temperature 0°C).

[0216] <Synthesis Example 3: Synthesis of Resin X3> A reaction vessel was charged with 83 g of polycarbonate diol ("C-2015N" manufactured by Kuraray Co., Ltd., number average molecular weight = 2000, hydroxyl group equivalent = 1000 g / eq.), 240 g of anisole as a solvent, and 14 g of isophorone diisocyanate (IPDI), and the temperature was raised to 50°C and the reaction was carried out for about 1 hour. Next, 145 g of oligophenylene ether resin containing phenolic hydroxyl groups at both ends ("SA90-100" manufactured by Sabic, hydroxyl group equivalent = 800 g / eq.) and 1 g of benzophenonetetracarboxylic dianhydride (BTDA) were added to the reaction mixture, and the mixture was heated to 140°C with stirring and reacted for about 4 hours. -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end of the reaction, and the reaction mixture was cooled to room temperature. The reaction mixture was then filtered through a 100-mesh filter cloth to obtain Resin X3 having an oligophenylene ether skeleton (non-volatile content 50% by mass, viscosity at 25°C 4.0 Pa s, weight-average molecular weight 254,000, glass transition temperature -4°C).

[0217] <Synthesis Example 4: Synthesis of Resin X'1> In a reaction vessel, 69 g of bifunctional hydroxyl-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3000, hydroxyl equivalent = 1800 g / eq.), 40 g of aromatic hydrocarbon mixed solvent ("IPZOL 150" manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin laurate were added and mixed to dissolve uniformly. When the mixture became uniform, the temperature was raised to 60°C, and 8 g of isophorone diisocyanate ("IPDI" manufactured by Evonik Degussa Japan Co., Ltd., isocyanate equivalent = 113 g / eq.) was added while stirring, and the reaction was carried out for about 3 hours. Next, 23 g of cresol novolak resin (DIC "KA-1160", hydroxyl equivalent = 117 g / eq.) and 60 g of ethyl diglycol acetate (Daicel) were added to the reaction mixture, and the mixture was heated to 150°C with stirring and reacted for about 10 hours. -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the reaction product was cooled to room temperature. The reaction product was then filtered through a 100-mesh filter cloth to obtain resin X'1 (phenolic hydroxyl group-containing butadiene resin: non-volatile component 50% by mass, glass transition temperature -4°C).

[0218] <Synthesis Example 5: Synthesis of Maleimide A> A MEK solution (70% by mass of non-volatile components) of maleimide A (n1=1.47, Mw / Mn=1.81) represented by the following formula, synthesized by the method described in Synthesis Example 1 of the Japan Institute of Invention and Innovation's Technical Journal Publication No. 2020-500211, was obtained. In Example 10 described later, it was blended as a compound having a radical polymerizable unsaturated group.

[0219] [ka]

[0220] [Examples 1 to 11, Comparative Examples 1 to 2] (1) Preparation of resin composition Each component was weighed according to the compounding composition shown in Table 1, and then 15 parts of MEK was added and mixed, followed by uniform dispersion using a high-speed rotating mixer to obtain a resin composition (resin varnish).

[0221] (2) Manufacture of Resin Sheet As a support, a polyethylene terephthalate film having a release layer (「AL5」manufactured by Lintec Corporation, thickness 38 μm) was prepared. Onto the release layer of this support, the obtained resin varnish was uniformly applied so that the thickness of the resin composition layer after drying would be 50 μm. Then, the resin composition was dried at 80°C to 120°C (average 100°C) for 4 minutes to obtain a resin sheet having a layer structure of resin composition layer / support.

[0222] (Evaluation of Elongation) The resin sheets obtained in the examples and comparative examples were heated at 200°C for 90 minutes to thermoset the resin composition layer. Next, by peeling off the support, a cured product of the resin composition layer was obtained. This cured product was subjected to a tensile test using a tensilon universal testing machine (「RTC-1250A」manufactured by Orientec Co., Ltd.) in accordance with Japanese Industrial Standard (JIS K7127), and the elongation at break (%) at 23°C was measured.

[0223] (Evaluation of MIT Test Flexural Resistance) The resin sheets obtained in the examples and comparative examples were heated at 200°C for 90 minutes to thermoset the resin composition layer. Next, by peeling off the support, a cured product of the resin composition layer was obtained. The cured product was cut out into a width of 15 mm and a length of 110 mm to obtain a test piece for evaluation. For each test piece for evaluation, using an MIT test apparatus (MIT flexural fatigue tester 「MIT-DA」manufactured by Toyo Seiki Seisakusho Co., Ltd.), a flexural test was conducted in accordance with Japanese Industrial Standard (JIS C-5016) under the measurement conditions of a load of 2.5 N, a bending angle of 90 degrees, a bending radius of 1.0 mm, and a bending speed of 175 times / min. The number of flexural cycles until the test piece for evaluation broke was measured. The measurement was performed on 5 test pieces, and the average value of the top 3 points was calculated.

[0224] (Measurement of Dielectric Loss Tangent) The resin sheets obtained in the examples and comparative examples were heated at 200°C for 90 minutes to thermally cure the resin composition layer. The support was then peeled off to obtain a cured product of the resin composition layer. The cured product was cut into a width of 2 mm and a length of 80 mm to prepare a test piece for evaluation. The dielectric loss tangent (Df value) of each evaluation specimen was measured by the cavity resonance perturbation method using Agilent Technologies' "HP8362B" at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C. Measurements were performed on three specimens, and the average value was calculated. The obtained average value was evaluated according to the following criteria. ×: Dielectric tangent is 0.01 or more ○: Dielectric tangent is less than 0.01

[0225] <Evaluation of insulation reliability> The resin sheets obtained in the examples and comparative examples were laminated on an imide film on which comb-tooth electrodes (line / space=15 μm / 15 μm) were formed, so that the resin composition layer of the resin sheet was in contact with the copper circuit surface, using a batch-type vacuum pressure laminator MVLP-500 (product name manufactured by Meiki Co., Ltd.). Lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing for 30 seconds at 100°C and a pressure of 0.74 MPa. After peeling off the polyethylene terephthalate film of the support, the laminate was thermally cured at 200°C for 90 minutes to obtain a laminate for evaluation of insulation reliability. The laminate for evaluation was placed in a highly accelerated life test device ("PM422" manufactured by Kusumoto Chemical Co., Ltd.) and the insulation resistance value of the laminate for evaluation was measured after 200 hours had elapsed under conditions of 130°C, 85% RH, and a voltage of 3.3 V. The measured values ​​were evaluated according to the following criteria. ○: Insulation resistance is 1.0×10 8 Ω or more ×: Insulation resistance is 1.0×10 8 Less than Ω

[0226] <Evaluation of adhesion to substrate> (1) Copper foil preparation The shiny side of Mitsui Mining & Smelting's "3EC-III" (electrolytic copper foil, 35μm) was immersed in MEC's ​​MEC Etch Bond "CZ-8101" to roughen the copper surface (Ra value = 1μm) and to apply anti-rust treatment (CL8300). This copper foil is called CZ copper foil. It was then heated in an oven at 130℃ for 30 minutes to obtain a CZ copper foil with a treated surface.

[0227] (2) Surface preparation of inner layer board A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") with an inner layer circuit formed was prepared. This laminate has copper foil as a conductor layer on the surface. Both sides of this laminate were immersed in MEC Etch Bond "CZ-8101" manufactured by MEC and etched by 1 μm to roughen the copper surface, producing an inner layer substrate. (3) Lamination of resin sheet Using a batch-type vacuum pressure laminator (two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.), the resin composition layer of the resin sheet obtained in the examples and comparative examples was laminated on both sides of the inner layer substrate so as to contact the inner layer substrate. The lamination process was carried out by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Next, a heat press was performed at 100°C and a pressure of 0.5 MPa for 60 seconds. Thereafter, the release PET support was peeled off to expose the resin composition layer. (4) Laminating copper foil and forming an insulating layer The treated surface of the CZ copper foil was laminated onto the exposed resin composition layer, and the resin composition layer was cured at 200°C for 90 minutes to form a cured product (insulating layer), producing a substrate with CZ copper foil laminated on both sides. This substrate was heated 10 times in a reflow device (Antom's "HAS6116", maximum temperature 260°C) to obtain an evaluation substrate.

[0228] (5) Measurement of copper foil peel strength (substrate adhesion) The evaluation board was cut into small pieces of 150 mm x 30 mm. A cutter was used to make a 10 mm wide and 100 mm long cut in the copper foil of the small piece, and one end of the copper foil was peeled off and held with a tensile tester gripper (TSE Autocom Universal Tester "AC-50C-SL") to peel off 35 mm in the vertical direction at a speed of 50 mm / min at room temperature (23°C). The load (kgf / cm) was measured in accordance with the Japanese Industrial Standards (JIS C6481) and evaluated according to the following criteria. ×: The measurement result of the adhesion to the base is less than 0.4 kgf / cm ○: The measurement result of adhesion to the base is 0.4kgf / cm or more

[0229] The results of Examples 1 to 11 and Comparative Examples 1 and 2 are shown in Table 1.

[0230] [Table 1]

[0231] The details of each component listed in Table 1 are as follows. <Thermosetting resin> HP-4032D: Naphthalene type epoxy resin, functional group equivalent weight approx. 142g / eq, manufactured by DIC Corporation YX7400N: Flexible epoxy resin, functional group equivalent weight approx. 450g / eq, manufactured by Mitsubishi Chemical Corporation HP-7200: Dicyclopentadiene type epoxy resin, functional group equivalent weight 259g / eq, manufactured by DIC Corporation <Hardening agent> KA-1160: Phenol-based hardener, cresol novolac resin, functional group equivalent 117g / eq, manufactured by DIC HPC-8000-65T: Active ester curing agent, functional group equivalent weight 223g / eq, non-volatile content 65% by mass in toluene solution, manufactured by DIC Corporation V-03: Carbodiimide curing agent, functional group equivalent weight 216g / eq, non-volatile content 50% by mass in toluene solution, manufactured by Nisshinbo Chemical Co., Ltd. <Resin X> Resins X1 to X3: Resins X1 to X3 synthesized in Synthesis Examples 1 to 3, anisole solutions with a non-volatile content of 50% by mass <Resin X'> Resin X'1: Resin X'1 synthesized in Synthesis Example 4, solution with 50% non-volatile content <Curing accelerator> 1B2PZ: Imidazole derivative, manufactured by Shikoku Chemical Industry Co., Ltd. <Compound having a radically polymerizable unsaturated group> BMI-689: Maleimide compound, Designer Molecules MIR-3000-70MT: Biphenyl aralkyl novolac type maleimide compound, a mixture of MEK solution with a non-volatile content of 70% and toluene, manufactured by Nippon Kayaku Co., Ltd. L-DAIC: Allyl group-containing resin, manufactured by Shikoku Chemical Industry Co., Ltd. <Inorganic filler> SO-C2: Spherical silica surface-treated with an amino-silane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5μm, specific surface area 5.8m2 / g, manufactured by Admatechs Co., Ltd.

Claims

1. thermosetting resin, Inorganic fillers, and Oligophenylene ether skeleton-containing resin X having a glass transition temperature of 25° C. or lower A resin composition comprising: A resin composition, the cured product of which exhibits a dielectric loss tangent Df of less than 0.01 and satisfies at least one of the following conditions (1) and (2): (1) Elongation is 5% or more but less than 50% (2) MIT folding endurance test: 200 or more folding cycles

2. The resin composition according to claim 1 , wherein the content of the resin X is 20% by mass or more and less than 85% by mass, when the resin component in the resin composition is taken as 100% by mass.

3. 2. The resin composition according to claim 1, wherein the content of the inorganic filler is 50% by mass or less when the nonvolatile components in the resin composition are taken as 100% by mass.

4. The resin composition according to claim 1, wherein the resin X comprises one or more structural units selected from the group consisting of polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic structural units, and polysiloxane structural units.

5. The resin composition according to claim 1 , wherein the resin X comprises a cyclic imide structure.

6. The resin composition according to claim 1, which is used for forming an insulating layer of a flexible substrate.

7. A cured product of the resin composition according to any one of claims 1 to 6.

8. A resin sheet comprising a support and a layer of the resin composition according to any one of claims 1 to 6 provided on the support.

9. The resin sheet according to claim 8 , wherein the support is a thermoplastic resin film or a metal foil.

10. A flexible substrate comprising an insulating layer made of a cured product of the resin composition according to any one of claims 1 to 6.

11. A semiconductor device comprising the flexible substrate according to claim 10.

Citation Information

Patent Citations

  • Multi-layer insulating film, method of manufacturing multi-layer insulating board and multi-layer board

    JP2015188073A

  • Resin composition, insulation film and semiconductor device using the same

    JP2016079354A

  • Resin composition for interlayer insulation layer, resin film for interlayer insulation layer, multilayer printed wiring board, semiconductor package and method for manufacturing multilayer printed wiring board

    JP2019123799A

  • Resin composition, sheet-like laminated material, printed wiring board, and semiconductor device

    JP2019210319A

  • Resin composition, cured product of resin composition, resin sheet, printed wiring board, and semiconductor device

    JP2021028368A